Data at the county level - Mabille, Geraldine; Stien, Audun; Tveraa, Torkild; Mysterud, Atle; Brøseth, Henrik; Linnell, John D. C. (Dryad Digital Repository, 2015)
The origin of the different variables is given in the article. The column headings refer to the variable names used in the article. The predator density is given per 1000 km2 and the roe deer density as the number of animal shot per 10 km2.